Tumor induced osteomalacia in head and neck region: single center experience and systematic review. Issue 10 (October 2019) - Shah, Ravikumar; Lila, Anurag R; Jadhav, Ramteke-Swati; Patil, Virendra; Mahajan, Abhishek; Sonawane, Sushil; Thadani, Puja; Dcruz, Anil; Pai, Prathamesh; Bal, Munita; Kane, Subhada; Shah, Nalini; et al.
Abstract : Tumor-induced osteomalacia in the head and neck region remains a challenging diagnosis to manage. Literature pertaining to management and outcome details remains sparse. We describe two cohorts: cohort 1 included seven patients from a single center in Western India with tumors located in paranasal sinuses ( n  = 3), intracranial ( n  = 2) and maxilla ( n  = 2). The unique features from our series is the management of persistent disease with radiation therapy ( n  = 2) and peptide receptor radionuclide therapy (PRRT) ( n  = 1). Cohort two has 163 patients identified from 109 publications for systematic review. Paranasal sinuses, mandible, intracranial disease, maxilla and oral cavity, in descending order, are reportedly common tumor sites. Within this cohort, mean age was 46 ± 14 years at presentation with 44.1% having local symptoms. Duration of symptoms varied from 1 to 240 months. Pre-surgery mean serum phosphorus was 1.4 ± 0.4 mg/dL and median FGF-23 levels were 3.6 (IQR:1.8–6.8) times of normal upper limit of normal. Majority (97.5%) were managed primarily with surgical excision; however, primary radiotherapy ( n  = 2) and surgery combined with radiotherapy ( n  = 2) were also reported. Twenty patients had persistent disease while nine patients had recurrence, more commonly noted with intracranial and oral cavity tumors. Surgery was the most common second mode of treatment employed succeeded by radiotherapy. Four patients had metastatic disease. The most common histopathological diagnosis reported is PMT mixed connective tissue, while the newer terminology 'PMT mixed epithelial and connective tissue type' has been described in 15 patients.